Punished for speaking up at the UN - Langrand, Michelle (Geneva Solutions, 2023)
Collaborating with the United Nations can have consequences, some more serious than others. Activists who have dared to denounce human rights abuses in their countries before the UN have faced smear campaigns. They have also been prevented from travelling, jailed or even killed in an attempt to stifle criticism.
Worldwide
Keywords: 2023-10 October